Theoretical study of interaction of heteroaromatic compounds with a cluster model of kaolinite tetrahedral surface. Issue 8 (20th February 2017) - Wang, Liang; Wang, Xing; Qian, Ping; Guo, Hong
Abstract: Heteroaromatic hydrocarbons (including thiophene [TH], benzothiophene [BT], and dibenzothiophene [DBT]) do not have apparent functional groups capable of interacting with the silica‐oxide tetrahedral surface of kaolinite. Thus, question remains concerning what would be the driving forces for the adsorption. Here, the Si13 O37 H22 cluster model for the surface is constructed, and the interactions of the surface with three heteroaromatic compounds are studied at the MP2/6‐31G(d, p)//B3LYP/6‐31G(d) level. The computed properties characterizing the complexes include optimized structural parameters, electron density characteristics (the ρ and ∇ 2 ρ values for CH…O bonds), adsorption energies, vibration frequencies and electrostatic potential maps. The results suggest that the CH…O hydrogen bonding interactions between the heteroaromatic compounds and tetrahedral surface are likely among the important interactions for the adsorption. The order of the stability of the cluster model of kaolinite complexed with the heteroaromatic compounds is found to be 3SiODBT > 3SiOBT > 3SiOTH based on the calculations. Abstract : Heteroaromatic hydrocarbons do not have apparent functional groups capable of interacting with the silica‐oxide tetrahedral surface of kaolinite. Thus, questions remain concerning the mechanism of that absorption. Ab initio calculations on model clusters of the kaolinite tetrahedral surface demonstrate that the hydrogen bond interactions involving the CH groups of heteroaromatic compounds and the oxygen atoms of kaolinite tetrahedral surface are among the key interactions for the adsorption.